Influence of Posture Variation on Shoulder Muscle Activity, Heart Rate, and Perceived Exertion in a Repetitive Manual Task. Issue 2 (3rd April 2017) - Luger, Tessy; Mathiassen, Svend Erik; Bosch, Tim; Hoozemans, Marco; Douwes, Marjolein; Veeger, DirkJan; de Looze, Michiel
Abstract : OCCUPATIONAL APPLICATIONS In repetitive work, more physical variation is believed to reduce the risk of eventually developing musculoskeletal disorders. We investigated the extent to which workstation designs leading to more variation in upper arm postures during a pick-and-place task influenced outcomes of relevance to musculoskeletal disorder risk, including muscle activity, cardiovascular response, and perceived exertion, measured through the maximal acceptable work pace. Posture variation to the extent obtained in our experiment had only minor effects on these outcomes, and considerably less impact than a moderate change in working height. Apparently, substantial manipulations of the workstation or of the work task will be needed to accomplish variation to an extent that can significantly change outcomes of relevance to occupational musculoskeletal disorders and, thus, represent a potential for reduction in musculoskeletal disorder risk. TECHNICAL ABSTRACT B ackground : Repetitive light assembly work is associated with an increased risk for developing work-related musculoskeletal disorders. More exposure variation, for instance by redesigning the workstation, has been proposed as an effective intervention. Purpose : We investigated the effect of upper arm posture variation in a 1-hour repetitive pick-and-place task on shoulder muscle activity, heart rate, and perceived exertion, measured on the Borg CR-10 scale and in terms of maximal acceptable work pace (MAWP). Methods : Thirteen healthy participants performed the task in three workstation designs where the hand was moved either horizontally (H30/30), diagonally (D20/40), or vertically (V10/50), with a mean upper arm elevation of ∼30°. In a fourth design, the hand was moved horizontally at ∼50° mean arm elevation (H50/50). Results : As intended, upper arm posture variation, measured by the upper arm elevation standard deviation and range of motion, differed between H30/30, D20/40, and V10/50. However, MAWP (10.7 cycles·min −1 on average across conditions; determined using a psychophysical approach), mean upper trapezius activity (54% reference voluntary exertion [RVE]), and heart rate (69 bpm) did not differ between these workstation designs. In H50/50, MAWP was lower (9.3 cycles·min −1 ), while trapezius activity (78% RVE) and perceived exertion (Borg CR-10) tended to be higher. Conclusions : Our results indicate that posture variation to the extent achieved in the current experiment leads to less effects on muscle activity and perceived exertion than a moderate change in working height.